PERSONAL COMMUNICATIVE CHARACTERISTICS OF CHILDREN OF JUNIOR SCHOOL AGE (World Bulletin of Social Sciences, 2023)
Learning the personal communicative characteristics of children of primary school age, The process of studying the personal communicative characteristics of children of primary school age